Anderkant etiek? Tradisie, dekonstruksie en verdere weë - Vosloo, R (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Beyond ethics? Tradition, deconstruction and the road ahead This article reflects on the critique against modernistic ethical theories. The question is asked: What lies beyond “ethics”? In order to deal with this question, the article discusses two influential strands in recent ethical discourse. The concepts of tradition and deconstruction are seen as heuristically helpful in the search for more adequate ethical methodologies. The main part of the paper engages with the work of Alasdair MacIntyre (in whose work the concept of tradition plays an important role) and John D Caputo (who makes use of the notion of deconstruction). While acknowledging the difference between these two strands, this article also seeks to find some convergence between the later work of MacIntyre and the focus on embodiment in an ethics of deconstruction (or deconstruction of ethics). Hence the focus on the importance of an ethic of vulnerable dependency as a challenge and resource for further ethical reflection and action.